Heuristics for multi-product capacitated disassembly lot sizing with lost sales. Issue 12 (2016) - Hrouga, M.; Godichaud, M.; Amodeo, L.
Abstract: Disassembly operations are the central stage of assembled product reverse logistic. As the environmental pressure on economic activities increases, reverse flows are more and more important and costly. Revenue obtained from disassembled components of a product can be low compared to disassembly cost and it can be interested to select the demand to meet or allow lost sales. In this paper, we propose an optimisation method for the multi-product capacitated disassembly lot sizing problem with lost sales which combines a genetic algorithm and a fix and optimise heuristic and which integrates heuristic to handle capacity constraint. Several test instances have been generated to evaluate the quality of the solutions compared to those obtained from previous methods.